Modelling of temperature fields in DP1000 steel during laser treatment using diffractive optical elements. Issue 1 (February 2021) - Bielak, R; Murzin, S P; Liedl, G; Otto, A; Kazanskiy, N L
Abstract: Diffractive optical elements (DOEs) with their unique properties allow to form a predetermined beam intensity profile in the focal plane. The use of DOEs in laser material processing technologies reveals new possibilities for controlling the properties and operational characteristics of processed parts. The beam intensity profile formed by DOE is presented in the form of an analytical expression that was used to set a surface heat source for modelling thermal processes in DP 1000 steel. Experimental studies of samples under laser heating were performed. Simulation output results correlate well with the experimental data. The proposed simulation model, based on a precise heat input definition, is an intermediate step to the final goal, which is the prediction of structural changes in the zone of laser beam irradiation.